Physical Examination of the Hip. (March 2021) - Wichman, Daniel; Rasio, Jonathan P.; Looney, Austin; Nho, Shane J.
The hip and pelvis have a complex anatomy and are a common source of pain and injury in the athletic population. The clinical examination of the hip requires a systematic approach to differentially diagnose hip problems with overlapping pain referral patterns. Because of the complex anatomy of the hip, the physical examination is a comprehensive evaluation of the 4 main pain generators of the hip from deep to superficial: the osteochondral, capsulolabral, musculotendinous, and neurovascular elements of the hip. The hip examination begins with the standing examination and gait analysis followed by a seated, supine, lateral, and prone examination. A targeted physical examination used in conjunction with a layered understanding of the hip and pelvis can help guide diagnostic testing, distinguish hip-specific diagnoses from similar presenting pathologies, and inform treatment.